2023
DOI: 10.1049/hve2.12335
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in multipactor physics and mitigation

Abstract: Recent progress made in the prediction, characterisation, and mitigation of multipactor discharge is reviewed for single‐ and two‐surface geometries. First, an overview of basic concepts including secondary electron emission, electron kinetics under the force law, multipactor susceptibility, and saturation mechanisms is provided, followed by a discussion on multipactor mitigation strategies. These strategies are categorised into two broad areas – mitigation by engineered devices and engineered radio frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 190 publications
0
4
0
Order By: Relevance
“…In this work, a different approach is proposed to blunt the avalanche of secondary electrons in the operation of a superconducting spoke cavity, employing higher-order modes. Although, multipacting suppression using a second carrier frequency has been asserted [10][11][12][13][14][15][16][17] quite often, but those were done in case of simple geometries (parallel plate and co-axial) only. Semenov et al [10] has made the first attempt [to the best of our knowledge] to investigate the multipactor phenomenon in a simple geometry of a one-dimensional metallic gap exposed to a homogeneous RF-field containing two carrier frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, a different approach is proposed to blunt the avalanche of secondary electrons in the operation of a superconducting spoke cavity, employing higher-order modes. Although, multipacting suppression using a second carrier frequency has been asserted [10][11][12][13][14][15][16][17] quite often, but those were done in case of simple geometries (parallel plate and co-axial) only. Semenov et al [10] has made the first attempt [to the best of our knowledge] to investigate the multipactor phenomenon in a simple geometry of a one-dimensional metallic gap exposed to a homogeneous RF-field containing two carrier frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma discharges have been a topic of continuous great interest because of their numerous applications in surface treatment and spectroscopy, space propulsion, environmental and agricultural fields, and plasma medicine [1][2][3][4][5][6][7][8][9][10][11][12][13]. They are * Authors to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The avalanche charges positively the dielectric surface, thereby producing a positive transverse electric field E x within a thin multipactor layer (the thickness of ∼10 µm) near the dielectric surface [38,39], as shown in figure 1(b). Out of this layer, E x is effectively shielded as the amount of positive surface charges on the dielectric surface should be equal to the negative space charges in the multipactor, which is known as the multipactor shielding effect [1,40]. The avalanche is saturated until the average secondary electron yield in a RF period reaches unity [5,33,39].…”
mentioning
confidence: 99%
“…Since the Guttons [40,41] and Farnsworth [42] first found the multipactor effects, numerous studies focused on the aforementioned two stages and provided a comprehensive understanding, including the susceptibility curve [1,[43][44][45][46], saturation [43,47,48], secondary electron emission avalanche [34][35][36][37] and mitigation strategies [49][50][51][52] in the first stage, discharge formation time [30] and plasma sheaths [33,[53][54][55] in the second stage. Recently, Wen et al [6,7,40] studied further the transient physics in the gas discharge stage by means of one-dimensional particle-in-cell (PIC) simulations along the transverse direction. They found that the interaction between secondary electrons and the produced plasma gives rise to the excitation of streaming waves.…”
mentioning
confidence: 99%